Age-related seroprevalence trajectories of seasonal coronaviruses in children including neonates in Guangzhou, China. (February 2023) - Luo, Yasha; Lv, Huibin; Zhao, Shilin; Sun, Yuanxin; Liu, Chengyi; Chen, Chunke; Liang, Weiwen; Kwok, Kin-on; Teo, Qi Wen; So, Ray TY; Lin, Yihan; Deng, Yuhong; et al.
Highlights: Seroprevalences of the four human coronaviruses (HCoVs) in children showed similar trajectories. Immunoglobulin G levels of the four HCoVs in mothers and their neonates were correlated. The immunoglobulin G in the neonates then dropped significantly until their 1 year of age. Majority of children were seropositive to the four HCoVs before 18 years old. Abstract: Objectives: Four seasonal coronaviruses, including human coronavirus (HCoV)-229E and HCoV-OC43, HCoV-NL63, and HCoV-HKU1 cause approximately 15-30% of common colds in adults. However, the full landscape of the immune trajectory to these viruses that covers the whole childhood period is still not well understood. Methods: We evaluated the serological responses against the four seasonal coronaviruses in 1886 children aged under 18 years by using enzyme-linked immunosorbent assay. The optical density values against each HCoV were determined from each sample. Generalized additive models were constructed to determine the relationship between age and seroprevalence throughout the whole childhood period. The specific antibody levels against the four seasonal coronaviruses were also tested from the plasma samples of 485 pairs of postpartum women and their newborn babies. Results: The immunoglobulin (Ig) G levels of the four seasonal coronaviruses in the mother and the newborn babies were highly correlated (229E: r = 0.63; OC43: r = 0.65; NL63: r = 0.69; HKU1: r = 0.63). The seroprevalences in children showed a similar trajectory in that the levels of IgG in the neonates dropped significantly and reached the lowest level after the age of around 1 year (229E: 1.18 years; OC43: 0.97 years; NL63: 1.01 years; HKU1: 1.02 years) and then resurgence in the children who aged older than 1 year. Using the lowest level from the generalized additive models as our cutoff, the seroprevalences for HCoV-229E, HCoV-OC43, HCoV-NL63, and HCoV-HKU1 were 98.11%, 96.23%, 96.23% and 94.34% at the age of 16-18 years. Conclusion: Mothers share HCoV-specific IgGs with their newborn babies and the level of maternal IgGs waned at around 1 year after birth. The resurgence of the HCoV-specific IgGs was found thereafter with the increase in age suggesting repeated infection occurred in children.